Climate Stress and Migration in India: An Exploratory Study of Environmental Changes on Population Movement (Journal of Informatics Education and Research, 2024)
This article delves into the intricate relationship between climate change and human migration in India, highlighting the severe impacts on marginalized communities. Climate change is causing rapid environmental shifts, particularly in regions like Kerala, Odisha, West Bengal, Uttarakhand, Bihar, and Maharashtra. These regions are experiencing a range of climate-induced phenomena, such as rising sea levels, desertification, increased frequency of cyclones, floods, and prolonged droughts. The consequent economic and social disruption has forced millions to migrate, often to urban centers where they face further challenges. The article also explores the plight of migrant laborers, especially women, who suffer from precarious working conditions, social discrimination, and exploitation, including trafficking and forced labor. In Kerala, coastal erosion and flooding have displaced entire communities, while Odisha's frequent cyclones and West Bengal's Sundarbans face rising salinity and loss of livelihood, pushing people into distress migration. The study highlights the urgent need for comprehensive policies to address the vulnerabilities of climate migrants, ensuring their rights, livelihoods, and social integration. This paper serves as a crucial resource for understanding the complex dynamics of climate migration in India and the profound socio-economic challenges it entails.